The Concept of Integration in Pedagogy of J. Laužikas - Vaitkevičius, Juozas (Acta Paedagogica Vilnensia, 1993)
The conception of the national school and the writings of interpreting the conception contain of a lot of talk about educational integration. This notion, though sounds new, is not new. The article gives an overview of a work by J. Laužikas remaining in a manuscript form “The Foundations of the Integration of Education", written in 1943 as habilitation thesis for receiving the title of a full professor. This theoretical work analyses the problem of education of the younger generation in the context of the nation, society, culture, as well as human nature. Laužikas anxiously stressed the process of cultural differentiation that inevitably affected the school. In his view, differentiation, rationality, and strict norms “turn the school into a sort of Procrustes bed”, which damages an integral person. A necessary condition in order to develop a coherent personality and society is integration of education, covering all educational moments: the structure of education and the educational process. In dealing with the problem of educational integration, Laužikas relies on the most advanced theories and paradigms of that time: German cultural pedagogy (Kerschensteiner, Petersen, etc.), the Anglo-Saxon integral pedagogy (Dewey, Kilpatrick, etc.), as well as behavioural, psychology (Thorndike, Watson, etc.), anthropological and existential philosophy.